2007
DOI: 10.1177/0887403406302327
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus Between Drug and Alcohol Treatment Program Integrity and Drug Court Effectiveness

Abstract: The literature supporting the efficacy of drug courts continues to grow. Much attention and research has focused on recidivism rates for participants, and generally address the question of, do drug courts work? The current state of drug court practice is a process that relies heavily on the drug and alcohol treatment services that are offered to clients. Many treatment programs, and the treatment philosophy that underlies their approach to solving substance abuse, offer vague and eclectic approaches that often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Ensuring that culturally competent, evidence‐based treatments are being offered to drug court participants may improve drug court graduation rates and potentially minimize the risk of having a violation within the first 30 days of drug court. When culturally competent, evidence‐based interventions are used in the treatment of substance use disorders, evidence has suggested that participants' engagement in treatment, motivation to change, and retention in treatment are improved (Beckerman & Fontana, ; Henggeler et al, ; Lutze & van Wormer, ). Additionally, studies have indicated that drug court participants who are engaged in treatment are more likely to graduate and not recidivate than participants who are not engaged in treatment (Banks & Gottfredson, ; Taxman & Bouffard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring that culturally competent, evidence‐based treatments are being offered to drug court participants may improve drug court graduation rates and potentially minimize the risk of having a violation within the first 30 days of drug court. When culturally competent, evidence‐based interventions are used in the treatment of substance use disorders, evidence has suggested that participants' engagement in treatment, motivation to change, and retention in treatment are improved (Beckerman & Fontana, ; Henggeler et al, ; Lutze & van Wormer, ). Additionally, studies have indicated that drug court participants who are engaged in treatment are more likely to graduate and not recidivate than participants who are not engaged in treatment (Banks & Gottfredson, ; Taxman & Bouffard, ).…”
Section: Discussionmentioning
confidence: 99%
“…The diverse range of participants accepted by drug courts makes it difficult to analyze practices nationwide, though it has been suggested that drug courts may not best serve those with the most serious addictions or use the hardest drugs, for whom more intensive and long-term inpatient treatment is indicated (Lutze and Wormer 2007; Wormer and Lutze 2010). Dirty urine screens and non-compliance to sentencing components result in sanctions of additional community service, fines, and ultimately jail time for multiple violations.…”
Section: The Justice System Response To Adolescent Addictionmentioning
confidence: 99%
“…Too often great innovations are lost to a failure to institutionalize good practice resulting in drift away from established missions, goals, and valuable program attributes. This drift often occurs when charismatic founders and program leaders move on to new positions, staff turnover disrupts an understanding of the existing program model and practice, and the institution does not adequately support innovative practice over time (see Lutze & van Wormer, 2007;Murphy & Lutze, 2009).…”
Section: Conclusion: Corrections Of Place Policy Considerationsmentioning
confidence: 98%